1957
DOI: 10.2307/4589806
|View full text |Cite
|
Sign up to set email alerts
|

Climate and Fluid Intake

Abstract: NUMEROUS investigators have studied the physiological reaction of adults to specific temperature,.humidity, and other variable climatic conditions (1, 2). These studies, initiated primarily by the U. S. Armed Forces, have been concerned largely with man's comfort, efficiency, or survival in the desert, arctic, or other places with severe climatic conditions. There have been a few investigations of the physiological response of children to heat stress under laboratory (3) and normal living conditions (4, 5), bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
1
1

Year Published

1971
1971
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 2 publications
0
60
1
1
Order By: Relevance
“…Existing data (Galagan et al, 1957;Walker et al, 1963) indicate that total fluid intake increases with age, but water consumption decreases with age. Galagan et al (1957) found that water intake per pound of body weight was highest among infants; it decreased with age, and varied directly with temperature.…”
Section: 2 Ingestion Of Fluoride From Drinking Watermentioning
confidence: 99%
“…Existing data (Galagan et al, 1957;Walker et al, 1963) indicate that total fluid intake increases with age, but water consumption decreases with age. Galagan et al (1957) found that water intake per pound of body weight was highest among infants; it decreased with age, and varied directly with temperature.…”
Section: 2 Ingestion Of Fluoride From Drinking Watermentioning
confidence: 99%
“…The optimal level for water fluoridation is between 0.7 and 1.2 mg/l, depending on the temperature of that area, prevent dental caries (Galagan et al, 1957;Galagan and Vermillio, 1957b). According to the annual average of maximum daily temperature in Taiwan (74-771F, CWB, 1999), the optimal fluoride concentration should be 0.8 mg/l for Taiwanese.…”
Section: Exposure and Risk Assessment Of Fluoride Intakes From Teamentioning
confidence: 99%
“…Findings indicated that a lower fluoride concentration was appropriate for communities in warmer climates because children drank more water on warm days. [60][61][62] Social and environmental changes, including increased use of air conditioning and more sedentary lifestyles, have occurred since the 1950s; thus, the assumption that children living in warmer regions drink more tap water than children in cooler regions may no longer be valid. 63 Studies conducted since 2001 suggest that children's water intake does not increase with increases in outdoor air temperature.…”
mentioning
confidence: 99%